Standardization of laparoscopic extrafascial hysterectomy: anatomic considerations to protect the ureter - Nyangoh Timoh, Krystel; Paquet, Caroline; Lavoué, Vincent; Touboul, Cyril; Fauconnier, Arnaud (Surgical and radiologic anatomy (English ed.), 2019)
Purpose To describe the procedure of laparoscopic extrafascial hysterectomy to avoid ureter injury. Methods Data were obtained from: (1) anatomic study of ten fresh female cadavers to measure the distance between the point where the ureter and uterine artery cross and the level of section of the ascending branch of the uterine artery during extrafascial dissection of the uterine pedicle and uterosacral ligament (Paris School of Surgery). The Wilcoxon test was used to compare measurements within each subject. P < 0.05 was considered to denote significance; (2) prospectively collected clinical data from women undergoing laparoscopic extrafascial hysterectomy from July 2006 to March 2014 at Poissy University Hospital, to describe the laparoscopic extrafascial hysterectomy technique with analysis of surgical complications using the Clavien–Dindo classification. Results Anatomic study: The mean (SD) distance between the point where the ureter and uterine artery cross and the level of the section of the ascending branch of the uterine artery were: 11.6 mm (5.2) in neutral position and 25 mm (7.5) after pulling the uterus laterally; and 25mm (8.9) after sectioning the ascending portion of the uterine pedicle and 38.6 mm (4.5) after complete uterine artery pedicle dissection through the uterosacral ligaments. After release of the ureter, the curve in front of the uterine artery disappeared. Clinical laparoscopic study: Sixty-eight patients underwent laparoscopic extrafascial hysterectomy. No ureteral complications occurred. Conclusion Laparoscopic extrafascial hysterectomy is a safe and feasible procedure. Combined lateralization and elevation of the uterus, section of the ascending branch of the uterine artery, and its extrafascial dissection along the uterosacral ligament contribute to protecting the ureter during the procedure.